Educação da mulher Bororo : caminhos formativos na educação escolar indígena em Mato Grosso - Campos, Neide da Silva (2021)
This research search for producing decolonial knowledges allied to the recognition of the “Southern Epistemologies” (SANTOS, 2010; 2011) which meaning is to systematize the own epistemologies which are not identified with the Western thought. The epistemic reading considers the reality tied to the cut of case studies referenced in ethnography concerning the formative processes of five Bororo educators in the state of Mato Grosso. This study aims at identifying the means which educate womenteachers in a matrilineal and matriarchal society which has been confronted, for three centuries, with the colonial processes crossed by Christian, patriarchal, sexist and authoritarian education as an expression of the non-indigenous place of speech. The context reveals the historical relationships and the ongoing strategies of neoliberal capitalism built in a more explicit and violent system on ancestral territories and cosmovisions. The research creates the intercultural dialogue necessary to comprehend the dynamics of a current society which looks for maintaining the centrality of women in keeping on the specific knowledge guaranteed by the transmission to new generations and the transitions of the worlds experienced between the living and the non-living human beings, conceived by the matrilineality of the lineage of clan tradition of the mother's home. The research was organized into two complementary exogamic halves from the Ecerae and Tugoarege clans, made up of four subclass, the society is structured in internal sociocultural relations and maintains knowledge and practices which are expressed on singing, dancing, adorning and body painting. Comprehending the body-woman-teacher in the Bororo matrilineal society and the transition from her place of holder and transmitter of traditional clan knowledge to that of a teacher who teaches the knowledge of Western, patriarchal society, in a school that is intended to be intercultural, was the main challenge assumed by the research. Based on that, it was done collaborative dialogues with five Bororo’s teachers carried out in their settlements/communities and in Cuiabá-MT mediated by the formative actions of the Project Action Indigenous Knowledge at School – UFMT Network. The study counted on semi-structured interviews, records of observations in a field notebook and authorized photographs. The matrilineal matrix of this millenary society marks and produces/reproduces a specific body of being a woman and being a man in a distinct approach, also due to the practices and knowledge shared in each sub clan. This education and cosmovision in which women are the centrality, however, does not exempt them from contradictions and gender perspectives, marked by the colonial process and the colonialities of thinking, being and power, which each community articulates, in a more autonomous way concerning their own processes of negotiations on the ethno-cultural borders of their territories and legacy of established historical relations. The school assumes a place of multiple experiences and perspectives for the collective emancipatory project of the Bororo people from epistemological colonialism, as well as, the imposing and authoritarian relationships which cross their expectations also in this context that expresses the presence of the State in the communities. The route taken by the Boe women - Bororo teacher, passes through the prestigious construction in the community which validates their place in the school, as the formative process of monitoring, election and choice of the professional formation. The protagonism of the woman Boe-teacher Boe, reveals the strength in the political struggle of the people when she assumes the dialogue with the national State, when she assumes the chiefdom, the school management and the pedagogical propositions supported by the epistemic domain of her cosmovision. The women teachers act especially when they leave the symbolic space of the domestic field and get into other sociocultural and political contexts, and they do it, from a collective care and need for their people, which is, recognizing themselves and being recognized from of the social place of a woman whose commitment maintains the clan matrilineal structure whose responsibility is to Boe's collectivity and cosmology.